Golden Jubilee Meeting of the Librarians - Üstün Yıldırım (Türk Kütüphaneciliği)
In the article 50th year meeting impressions have been shared of the students enrolled in 1964 to Ankara University Faculty of Language, History and Geography Department of Librarianship.